Microstructure and mechanical characterization of semisolid metal components for wrought aluminium alloys - Ahmad, Asnul Hadi; Ishak, M.; Rashidi, Maarof Mohd; Romlay, Fadhlur Rahman Mohd; Zakri, Ghazali; Ahmad Shah, Luqman Hakim (2018)
This research present the works on the behaviour of wrought aluminium alloy via semisolid metal processing. Proper setting of pouring temperature and holding times is one of the important factors to obtain better microstructure formation and mechanical properties. In this work, thermal analysis experiments were conducted in order to obtain thermal profile of wrought aluminium alloy. This thermal analysis results such as liquidus, eutectic and solidus temperatures then were used as input parameters for subsequence experiments. In Direct thermal method (DTM) experiments, molten aluminium alloy was poured into copper tube moulds and cooled down to the semi-solid temperature before quenched in water at room temperature. The parameters of pouring temperature and holding times used were at 685 ℃, 665 ℃, 64 5℃ and 60 s, 40 s and 20 s respectively. The parameters used in DTM were purposely to study the effect on metallography and mechanical properties of aluminium alloy. Experimental results have proven that the solidified microstructure shown that, microstructure with smaller grain size has better hardness strength compared to bigger grain size. These results were represented with sample that processed with longer the holding time produced smaller grain size. The metallography analysis results was also found that the smallest microstructure formation and the hardest among samples was achieved at the sample with pouring temperature at 645 ℃ and holding time at 60 s. Result obtained from this research is very useful in order to understand aluminium behaviour which processed via semisolid metal processing route.